Tissue transglutaminase is involved in the inflammatory processes of active chronic gastritis - Riezzo, Giuseppe; Orlando, Antonella; Clemente, Caterina; D'Attoma, Benedetta; Valentini, Anna Maria; Armentano, Raffaele; Giorgio, Pietro; Pisani, Antonio; Russo, Francesco (Archives of Biological Sciences, 2021)
Paper description: Transglutaminase 2 exerts multifunctional activities and acts as an inflammation marker produced by activated macrophages in several chronic conditions, including gastritis. The concentrations of transglutaminase 2 and inflammation markers, as well as macrophage score, were measured in the supernatant of gastric antrum biopsies. Transglutaminase 2, interleukins 8-10, tumor necrosis factor-α and toll-like receptor-4 were significantly higher in active than inactive chronic gastritis, while interleukin-6 was significantly lower in the active form. The macrophage score and interleukin-10 correlated positively. Transglutaminase 2 is involved in the pathophysiology of chronic gastritis, specifically the active one. Its inhibition could prevent the progression of gastritis. Abstract: Since tissue transglutaminase-2 (TG2) can represent a marker of inflammation for some gastrointestinal (GI) diseases, we aimed to evaluate TG2 and inflammatory markers’ mucosal content in gastric antrum biopsies to shed light on the histological and biochemical background of chronic gastritis inflammation. Fifty-one of 78 patients who underwent upper GI endoscopy (UGIE) for dyspeptic symptoms, had a gastric biopsy. The symptom profile was assessed by a GI symptom rating scale (GSRS) score. Thirty-five patients (69%) showed chronic gastritis. TG2, interleukin-6 (IL)-6, IL-8, IL-10, tumor necrosis factor (TNF)-α, lipopolysaccharides (LPS) and toll-like receptor (TLR)-4 were evaluated in serum and the culture medium of gastric biopsies. TG2, IL-8, IL-10, TLR-4 and TNF-α were significantly higher in active chronic gastritis than in the inactive one and were linked to macrophage concentration. IL-6 was significantly lower in the active form of chronic gastritis than in the inactive one and negatively correlated with TG2. Lastly, IL-10 significantly correlated with the macrophage score. TG2 can exert an active role in chronic gastritis pathogenesis by cooperating with different markers of inflammation. It seems that TG2 can represent a possible therapeutic target for modulating inflammation and disease progression.